Prediction of Extreme Sea Water Waves at Ancol Beach Using ID3 Algoritma Algorithm - Arum Budi Harti; Dionysius Hendard Christianto; Renata Nabillah; Mutiara Oktavia (Institute of Computer Science (IOCS), 2022)
Ocean waves are natural events where water waves gradually move up and down. This regular rise and fall of water is one of the important aspects of transportation, predicting potential trade disasters and tsunamis in water areas. Know the data The future beyond the level of ocean waves can bring great benefits smoothly Transport and trade of territorial waters. Future data can be obtained from forecasts with certain algorithms. The ID3 algorithm is one of the most common learning algorithms. Used to create a decision tree or decision tree. The result of this analysis is a decision tree that can be used for classifying sea level using an accuracy of 88%.